Book review of: Mariotti, Ilaria; di Vita, Stefano; Akhavan, Mina (Hrsg.) (2021): New workplaces – Location patterns, urban effects and development trajectories. A worldwide investigation - Schmidt, Suntje (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Book review.